The “Inverted U” Hypothesis: Evidence from Indian Height Data - Brennan, Lance; McDonald, John (Journal of Income Distribution®, 2001)
Stature can be a useful indicator of living standards, particularly when income and wage data are scarce or of poor quality, as is often the case for undeveloped rural economies with large self-employed sectors. This study shows that Indian height data provide some supporting evidence for widening inequality in the initial phase of the development process. This corresponds to the more contentious part of the “Inverted U” hypothesis, which asserts that income inequality initially increases, then declines, during the development process.